ROLE OF NAVGRAHA PLANTS IN MANAGEMENT OF NON- COMMUNICABLE DISEASES - Chandni, *Gupta; Navneet, Sharma (International Journal of Ayurveda and Pharma Research, 2017)
Non-communicable diseases (NCDs), mainly cardiovascular diseases, cancers, diabetes, obesity and chronic respiratory diseases, represent a leading threat to human health and human development in todays world. Medicinal plants have always been the principle sources of medicine worldwide. Ayurvedic medicines share the millennia of Ayurvedic herbs which prevent and effectively treat many non-communicable diseases. These drugs are safe, effective and affordable. We cannot limit the study of Indian plants based on their therapeutic values but we should also consider their use from Astrological point of view. As we all know, in astrology it is believed that there are nine planets which are controlling the destiny of a person and there are certain specified herbs which act as a remedy to treat disastrous effect of planets. To minimize the ill effect of Navgrahas one of the easiest methods is to plant the Navgrah Vatika (garden). It protects from various problems including non-communicable diseases. Astrology along with Ayurveda shows how we can heal ourselves through the herbs corresponding to their particular star. Combining astrology and Ayurveda fruitful results can be obtained. Each plant in this paper corresponds to that particular planet/star which gives energy to that particular person born during that particular star time. Present paper will describe the importance Navgrahavatika, role of planets in health and how these Navgraha plants are useful in prevention and treatment of non-communicable diseases.